IMPACT PATHWAYS FROM AGRICULTURAL POLICY TO IMPROVED NUTRITION OUTCOMES: THE CASE OF THE PROMISE PROJECT IN NORTHEASTERN GHANA - Abazaami, J.; Atuik, E. A.; Dasoberi, V. N. (UDS International Journal of Development, 2019)
This paper strives to add to continuing effort at many establishments envisioned at determining urgent knowledge openings, outlining the finest research slants needed to plug those gaps, and investigating how to improve policy and programme implementation in agriculture with comprehensive empirical evidence of ‘what works’ for improved nutrition outcomes under which circumstances and why. The study attempted to do this by specifically examining CARE International’s Linking Initiatives, Stakeholders and Knowledge to Achieve Gender-Sensitive Livelihood Security (LINKAGES) programme (PROMISE Ghana). Analysis was focused on the Women’s Empowerment in Agriculture Index (WEAI) and the Logical framework for assessing impact of agricultural interventions on nutrition (as proposed by Masset et al. 2011). Findings of the paperpoint to evidence of improved nutrition; reinforced and expanded livelihoods; improved food sources and diversity; expansion and protection of key assets; shifts in gender dynamics that have fostered and promoted women’s agency etc. These findings to a large extent give endorsement to the Framework for Action that emerged from the Second International Conference on Nutrition that culminated in the launch of the UN Decade of Action on Nutrition (2016–2025). The findings also strongly layout rigorous empirical information to inform policymakers in Ghana on what kinds of agriculture to invest in (through research or programming) that will have positive benefits for nutrition outcomes and livelihood security, particularly among mothers and children – thus, underscoring the importance of improved policy targeted at making agriculture work for nutrition in Ghana. Keywords: Nutrition, Ghana, Agricultural Policy,Livelihood Security